2022
DOI: 10.3390/gels8060365
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Nanoparticles for Targeted Dual Drug Release out of Alginate-di-Aldehyde-Gelatin Gels

Abstract: The aim of the present work was to develop a dual staged drug release of an antibiotic (clindamycin) and a growth factor: bone morphogenetic protein-2 (BMP-2) from a biodegradable system consisting of hydrogel and gelatin nanoparticles (GNP). Two-step de-solvation allowed us to prepare GNPs (~100 nm) as drug carriers. Fluorescein isothiocyanate (FITC)-conjugated protein A was used as a model substance for BMP-2. A 28-day release experiment was performed to determine the release kinetics from GNP for both FITC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Comparatively, ADA gelatin gel has exhibited superior mechanical properties when incorporated into β-TCP ceramic and demonstrated higher biodegradability than pure alginate [ 32 ]. Given its prior assessment for drug release [ 31 , 33 ], ADA gelatin gel emerges as a promising hydrogel for targeted and controlled drug delivery. Daptomycin, a relatively new antibiotic in the gram-positive spectrum, and BMP-2, a substance that promotes bone healing, are of interest for local application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, ADA gelatin gel has exhibited superior mechanical properties when incorporated into β-TCP ceramic and demonstrated higher biodegradability than pure alginate [ 32 ]. Given its prior assessment for drug release [ 31 , 33 ], ADA gelatin gel emerges as a promising hydrogel for targeted and controlled drug delivery. Daptomycin, a relatively new antibiotic in the gram-positive spectrum, and BMP-2, a substance that promotes bone healing, are of interest for local application.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by dipping, dropping or spraying [26]. The literature has previously documented a delayed in vitro drug release from a carrier system [27], comprising microporous β-TCP ceramic and alginate [28][29][30][31]. Comparatively, ADA gelatin gel has exhibited superior mechanical properties when incorporated into β-TCP ceramic and demonstrated higher biodegradability than pure alginate [32].…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by dipping, dropping or spraying [26]. The literature has previously documented a delayed in vitro drug release from a carrier system [27], comprising microporous β-TCP ceramic and alginate [28][29][30][31]. Comparatively, ADA gelatin gel has exhibited superior mechanical properties when incorporated into β-TCP ceramic and demonstrated higher biodegradability than pure alginate [32].…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, ADA gelatin gel has exhibited superior mechanical properties when incorporated into β-TCP ceramic and demonstrated higher biodegradability than pure alginate [32]. Given its prior assessment for drug release [31,33], ADA gelatin gel emerges as a promising hydrogel for targeted and controlled drug delivery. Notably, the potential for dual drug release in this system remains unexplored, representing an avenue for enhancing patient outcomes by combining anti-infective treatment, bone growth promotion therapy, and improved bone stability facilitated by the β-TCP ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…Another review article [33] discussed soft tissue repair using nanoparticle-modified biocompatible polymers including hydrogels. Schrade S et al [34] found that gelatin nanoparticles can be used for targeted dual drug release out of aleginate-di-aldehyde-gelatin gels. Calcium magnesium silicate (CaO-MgO-SiO 2 )-based bioceramics, containing bioactive phases of diopside, akermanite, and merwinite, were prepared by Alecu AE et al [35] using the solgel method followed by thermal treatment.…”
mentioning
confidence: 99%